Proces wzmacniania unii gospodarczej i walutowej w konteśkcie kryzysu w stgrefie Euro (Politeja, 2015)
Process of strengthening of the Economic and Monetary Union in the context of the crisis in the euro areaThis article includes a description and an assessment of the key initiatives dedicated to strengthening the economic pillar of the Economic and Monetary Union (EMU) and puts emphasis on reform of the economic governance framework. As was pointed out, the crisis in the euro area has been the most important incentive to deep reshape construction of the EMU, especially in respect to its economic governance. This process – being, beside rescue actions, one of the dimensions of the response to the crisis in the euro area – has multistage and multidimensional character. The new solutions in this dimension, which encompass: the European semester, the “six‑pact”, the “two‑pact”, the Treaty on Stability, Coordination and Governance in the EMU (TSCG), European Stability Mechanism (ESM), Single Supervisory Mechanism (SSM) and the Single Resolution Mechanism (SRM), strengthened economic pillar of the EMU. Above‑mentioned solutions can improve resilience of the EMU on risks of crises in the future, however these instruments do not provide a guarantee that this area will be instability free zone. Creation of the fiscal capacity mechanism would be important for reinforce the abilities of the EMU to counteract potential disturbances. The treaties change will be required for the completion of the EMU.